The Effect Of Return On Equity (Roe) On Stock Returns Through Stock Transaction Volume (Case Study Of Companies Listed On The Lq45 Index For The 2019-2023 Period) - Dodi Siswanto; Dini Ihtisam; Harland Yusuf (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The purpose of this study was to determine the effect of Return on Equity (ROE) on Stock Returns through Stock Transaction Volume. Research data comes from secondary data from both the Indonesia Stock Exchange (IDX) and yahoo finance. The population in this study is secondary data from companies listed on the Indonesia Stock Exchange (IDX) which are listed on the LQ45 index with the sample limited to annual data for the period 2019 - 2023, with a total of 225 data. The data analysis method used in this research is the panel data regression method. The results show that the Return on Equity (ROE) variable has a significant effect on stock returns, the Return on Equity (ROE) variable has a significant effect on the volume of stock transactions, the ROE variable has a positive and significant effect on stock returns, the volume of stock transactions has a positive and significant effect on stock returns, and the Stock Transaction Volume Variable (Z) is able to mediate the effect of the ROE Variable (X) on the Stock Return Variable (Y). Keywords: Return on Equity (ROE), Stock Return, Stock Transaction Volume